The Legal Protection of Geographical Indications in Indonesia Towards The Asean Economic Community - Wahyu Sasongko (UBL, 2013)
Geographical Indications is a regime of Intellectual Property Rights which is relatively new not only forIndonesia but also for international scope. Geographical Indications is giving legal protection for a groupof producers who produce goods which have high qualities and is not intended for individual.Geographical Indications are relevant to goods production yielded by the ASEAN countries which tend tohave a similarity that can potentially generate conflicts. Meanwhile, regulation of GeographicalIndications in Indonesia has differences from other ASEAN countries such as Malaysia, Singapore, andThailand. If this matter is not anticipated immediately the plan to establish the ASEAN EconomicCommunity in 2015 will face obstacles. Through the understanding of legal protection of GeographicalIndications in Indonesia, hopefully it will bring benefits to reach the ASEAN Economic Community.